Composition and catch number of fish landings on the eastern coast of the Aceh region. Issue 1 (February 2021) - Fadli, N; Syafruddin, S; Hasibuan, P; Sofyan, SE; Rianjuanda, R; Syukri, M; Saidi, T; Dawood, R
Abstract: Information on the composition and number of catches that comprise fish landings is an essential component of fisheries management. Because such data is especially limited with regard to the eastern coast of the Aceh region of Sumatra, the present study examined fish landing characteristics for this region. Data were collected from November 24 to December 24, 2019, in seven fish landing sites (TPI) in three districts (Aceh Utara, Bireuen, and Lhokseumawe) on the eastern coast of the Aceh region. Fishes were recorded daily in each TPI during the study period, and a total of 32 fish categories were identified. Pelagic fish dominated the catch: longtail tuna, scad, island mackerel, yellowfin tuna, Carangidae, frigate tuna, skipjack tuna, albacore, kawakawa, and white snapper were the most landed fish during the survey period. The study also showed marine fisheries production to be 181, 994 kg/month, or an average of 7, 000 kg/day. Across the three districts, Bireuen had the highest fisheries production (122, 683 kg), followed by Aceh Utara (35, 092 kg), and Lhokseumawe (24, 220 kg). This study provides baseline data that will be valuable in developing an effective fisheries management strategy plan in the region.